Clinical Evaluation of Intraoral Suture Patterns Using Poliglecaprone 25 in Greyhound Dogs. (June 2022) - Pegg, Jane E.; Hoyer, Naomi; Kelley, Jennifer L.; Weir, H.; Rawlinson, Jennifer E.
To evaluate healing and complications of extraction sites closed with a simple interrupted pattern (SI) and a simple continuous (SC) suture pattern in a prospective randomized clinical trial. Greyhounds were selected from a rescue with a standardized environment and naturally occurring disease. Surgical extractions were performed (35 sites) and all mucogingival flaps were closed with 4–0 poliglecaprone 25 using either SI or SC randomly assigned by surgical site. Oral healing/dehiscence, suture inflammation, suture loss, accumulation of debris, presence/nature of discharge, necrotic tissue and adjacent contact ulceration were evaluated. Fisher's exact test was used to compare categorical data and two-tail T tests used to compare continuous data. Results showed SC was faster to apply. No new dehiscence events were detected after Recheck 1. There was no significant difference for dehiscence scores between SI and SC. A trend was seen towards more major dehiscence in the SI group. This study concluded SC is an alternative to SI for closure of occlusal surfaces in the mouth. Mandibular canine tooth extraction sites were more likely to have a high dehiscence score than all other sites combined regardless of surgical technique.